Plasticity of the Nb-rich μ-Co7Nb6 phase at room temperature and 600°C - Luo, W; Xie, Z; Sun, P-L; Gibson, JSK-L; Korte-Kerzel, S (Elsevier, 2023)
The µ phase is a common precipitation phase in superalloys and it exists in a wide composition and temperature range. As such, we study the influences of composition and temperature on its plasticity by micropillar compression tests and transmission electron microscopy. The micropillars of the μ-Co7Nb6 phase deform plastically by basal slip at room temperature and 600 °C. At room temperature, the Co-49Nb and Co-52Nb micropillars show high yield stresses and an abrupt large strain burst at the onset of yielding regardless of orientation, whereas the Co-54Nb micropillars oriented for basal slip yield at much lower stresses and show intermittent small strain bursts during plastic deformation. While the Co-49Nb micropillars deform by full dislocation slip on the basal plane at room temperature, the Co-54Nb micropillars deform by partial dislocation slip on the basal plane. At 600 °C, the Co-49Nb micropillars oriented for basal slip show stable and continuous plasticity and their critical resolved shear stresses decrease dramatically. In contrast to the full dislocation slip at room temperature, the plastic deformation of the Co-49Nb micropillars occurs via partial dislocation slip on the basal plane at 600 °C. Based on the geometric γ-surfaces for all potential basal slip planes, we explore where and why the glide of full and partial dislocations on the basal plane occurs in the μ-Co7Nb6 phase.